The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1063/1.454792
|View full text |Cite
|
Sign up to set email alerts
|

Pressure dependence of the elastic constants of ice Ih to 2.8 kbar by Brillouin spectroscopy

Abstract: The adiabatic elastic constants of single crystals of ice Ih from the Mendenhall Glacier, and the longitudinal and transverse speeds of sound of polycrystalline ice aggregates, have been measured in the range 0–2.8 kbar at −35.5 °C by Brillouin spectroscopy. The ice was held in a 10 kbar optical cell that allowed the sample to be rotated under loads of up to 10 kbar about one axis from outside the cell. The elastic constants C11, C12, C13, C33, and C44, and the bulk modulus are quadratic in the pressure range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
66
3

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 11 publications
15
66
3
Order By: Relevance
“…Pure dioctyl sebacate was initially used as the hydraulic fluid. However, contrary to previous claims that the fluid remains clear to −35°C and 300 MPa, 8 we found pure dioctyl sebacate clouded below ϳ10°C at the lowest pressures employed ͑50 MPa͒. This may have been due to the presence of the silicone, which was found to gel irreversibly at moderate pressures, and at the lowest pressure at temperatures below the freezing point of water.…”
Section: E Hydraulic Fluidcontrasting
confidence: 85%
See 1 more Smart Citation
“…Pure dioctyl sebacate was initially used as the hydraulic fluid. However, contrary to previous claims that the fluid remains clear to −35°C and 300 MPa, 8 we found pure dioctyl sebacate clouded below ϳ10°C at the lowest pressures employed ͑50 MPa͒. This may have been due to the presence of the silicone, which was found to gel irreversibly at moderate pressures, and at the lowest pressure at temperatures below the freezing point of water.…”
Section: E Hydraulic Fluidcontrasting
confidence: 85%
“…7 observed that DOS remained clear to −35°C and 300 MPa. 8 We found dioctyl sebacate alone clouded below ϳ10°C at the lowest pressures employed ͑50 MPa͒. This may have been due to the presence of the silicone grease used to seal the sample cuvette.…”
Section: Maintaining An Optically Neutral Pressure Mediummentioning
confidence: 94%
“…For this pressure range we assume a linear P-V relationship and B 0 0 is fixed at 4. The fitting results shows that the unit cell volume for Ar filled-ice at zero pressure (V 0 ) should be around 317 Å 3 , and the bulk modulus at zero pressure (B 0 )i s 11.7 ± 0.4 GPa, which is greater than that of ice-Ih (8.97 GPa [29]). Previously, the bulk modulus of methane filled-ice was calculated by Hirai et al [27] (15.4 GPa) and Loveday et al [30] (15.2 GPa).…”
Section: Resultsmentioning
confidence: 99%
“…Published data on ice compressibility vary up to a factor of 3.6 between different authors. In TEOS-10, the related uncertainty of mechanical measurements could be reduced by a factor of 100 to about 1 % Wagner, 2004, 2005) using crystallographic spectroscopy data (Gammon et al, 1980Gagnon et al, 1988); see Fig. 2.…”
Section: Gibbs Function Of Ice Ihmentioning
confidence: 99%